2020
DOI: 10.1001/jamanetworkopen.2020.30898
|View full text |Cite
|
Sign up to set email alerts
|

Association of Burnout With Depression and Anxiety in Critical Care Clinicians in Brazil

Abstract: IMPORTANCEIt is unclear whether burnout, anxiety, and depression constitute the same or different constructs. Better understanding of these constructs is important for diagnosis and treatment for intensive care unit (ICU) clinicians. OBJECTIVE To determine the associations and distinctiveness of burnout, depression, and anxiety in a sample of ICU clinicians. DESIGN, SETTING, AND PARTICIPANTS This cross-sectional study used baseline data from the ICU Visits Study, a cluster-randomized crossover clinical trial c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
3
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 42 publications
0
23
3
3
Order By: Relevance
“…Studies have mentioned that physical and mental diseases affect psychological symptoms and burnout 15 , 31 . We excluded participants with uncontrolled chronic diseases and mental and sleep disorders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have mentioned that physical and mental diseases affect psychological symptoms and burnout 15 , 31 . We excluded participants with uncontrolled chronic diseases and mental and sleep disorders.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, a non-linear relationship was found between burnout and age, with employees aged 30–40 having higher burnout than other age group 13 . A systematic review and meta-analysis study have revealed that depression and anxiety could cause burnout among HCWs and different types of workers (such as teachers or firefighters) 15 , 16 . Thus, we suspected that psychological symptoms or severe physical diseases might also affect different burnout domains that are not directly related to emotional changes.…”
Section: Introductionmentioning
confidence: 99%
“…Burnout nos profissionais envolvidos no cuidado intensivo, sendo os mais apontados: sexo, idade, anos de experiência de trabalho e alta carga horária (FISCHER et. al, 2020;CHUANG, 2016;HU et al, 2016).…”
Section: Os Estudos Analisados Indicaram Alguns Fatores Em Comum Para O Desenvolvimento Dounclassified
“…11 terem salários inferiores e sofrerem mais demanda no trabalho (CRUZ, 2019). Seguindo tal sugestão, estudos analisaram também as mulheres no meio hospitalar com um risco para burnout bem maior (FISCHER et. al, 2020;CHUANG, 2016).…”
Section: Os Estudos Analisados Indicaram Alguns Fatores Em Comum Para O Desenvolvimento Dounclassified
“…Um estudo realizado no final de 2020 verificou que cerca de 77% dos profissionais de saúde tiveram sintomas relacionados a SB, sendo que mais de 80% destes profissionais atuavam diretamente no enfrentamento à pandemia, o que pode significar um agravamento da doença durante o cenário pandêmico. Destaca-se ainda o fato de que o quadro de saúde dos trabalhadores da linha de frente, reflete também em maiores chances de erros relacionados a assistência o que gera danos aos pacientes e instituição de saúde (FISCHER et al, 2020).…”
Section: Introductionunclassified